Da relativização da coisa julgada - Cerqueira, Luciana Castro Gomes (2014)
This work pretends to discuss about the relativization of res judicata in light of the Brazilian civil procedural law, as it is a routine issue, but nearly a decade ago, still arouses crisis on the real concept of relativity to the res judicata. The desire to discuss the subject started in class of pos-graduation in procedural law in PUC/COGEA in São Paulo when most of the students and lawyers defends that the res judicata should be disregarded and must not be covered by the constitutional protection. In the sphere of jurisprudence, the issue is still not clearly defined in the Supreme Court, where it´s possible to find cases in favor of the flexibily of the res judicata, and cases that they don´t accept it. As this is a topic of great paradoxes faced by activists of the right before the Brazilian courts, considering that full acceptance may undermine legal certainty, while its complete denial legitimizes injustice, is not intended to humble this research work exhaust it, but only addressing some of the major aspects of the fence, despite those who advocate the theory that res judicata does not have absolute character in the Brazilian legal system, forward the arguments espoused by the current that defends the absolute character of res judicata by reason of legal, finally the arguments of those who advocate easing. With this goal, we will analyze the mechanisms of procedural flexibility under Brazilian law, the livelihood of the quarrella nullitatis parental legal system and other important aspects of the subject, seeking help for the growth of the discussions, within the perspective of the legal system in force